Correlation and Path Analysis Studies in Pigeon Pea (Cajanus cajan (L.) Millsp.) Genotypes under Foothill Conditions of Nagaland - Devi, Oinam Priyadarshini; Sharma, Malini Barthakur; Seyie, Kigwe; Ozukum, Chubatemsu (International Journal of Bio-resource and Stress Management, 2020)
Correlation coefficient and Path coefficient analysis were evaluated in eleven Pigeon Pea genotypes along with one check variety under the research field of Genetics and Plant Breeding Medziphema, Nagaland, India during kharif season 2017-2018 and the data were recorded on nine quantitative characters. The correlation studies showed that, seed yield plant-1 showed significant and positive correlation with secondary branches plant-1 both at phenotypic and genotypic level and at genotypic level with number primary branches plant-1, number of secondary branches plant-1, number of pods plant-1 and test weight respectively. In path coefficient analysis, number of pods plant-1 exhibited high and positive direct effect on seed yield plant-1 followed by number of secondary branches plant-1 and days to maturity. Negative direct effect was exhibited by number of primary branches plant-1 for seed yield plant-1. Number of primary branches plant-1 and number of seeds pod-1 showed high indirect effect through number of pods plant-1. The study on the correlation and path analysis concluded that out of the eleven genotypes, PA-291 can be used as a promising genotype since it exhibited high number of primary and secondary branches, high number of pods plant-1, high test weight and high seed yield plant-1. And the genotypes viz. UPAS-120 which takes the least days to flower and shortest height, PA-421 which has the maximum test weight and PA-441 which have the maximum pods plant-1 may be considered as potential genotypes for incorporation in pigeon pea breeding programme.